Optimization and Characterization of Epoxidized Palm Oil-Based Epoxy Polymers: Structure-Property Relationships for Sustainable Material Applications - Buran, Abayhan; Durgun, Murat Ersin; Aydogmus, Ercan; Topdemir, Aykut (Wiley, 2026)
This study develops a tunable bio-based epoxy platform by converting commercially available palm oil into an epoxy-functional renewable modifier and systematically linking processing parameters to final material performance. The epoxidation of palm oil is optimized using response surface methodology (RSM) by varying temperature (45 degrees C-65 degrees C) and reaction time (2-6 h), and the optimum conditions are identified as 64.56 degrees C and 5.91 h in a PID-controlled reactor. Under these conditions, a maximum epoxidation efficiency of 80.98% is achieved with excellent model reliability (R 2 = 0.9918, adjusted R 2 = 0.9886, C.V. = 0.4575%). The resulting modified palm oil (MPO) is incorporated into a commercial epoxy resin at 0wt%, 15wt%, 30wt%, and 45wt% and cured to form sustainable epoxy networks. Characterization demonstrates that increasing MPO content progressively decreases bulk density (+/- 4 to 6 kg/m3), Shore D hardness (+/- 2 to 3), tensile strength (+/- 1 to 2 MPa), thermal conductivity (+/- 0.002 to 0.004 W/m K), and dielectric constant (+/- 0.02 to 0.04), while significantly increasing elongation at break (+/- 0.8% to 1.5%). These trends indicate a controlled transition from rigid to ductile behavior due to dilution of the aromatic epoxy network by flexible aliphatic chains and a corresponding reduction in crosslink density. FTIR spectroscopy confirms successful epoxidation through the loss of C=C bands and the appearance of epoxy C-O-C vibrations, whereas SEM reveals homogeneous morphologies at low MPO levels and phase separation at higher loadings. Curing kinetics slow with increasing MPO, reaching up to 48 h at 55 degrees C compared with 24 h for neat epoxy. Overall, this optimized and scalable route enables the design of eco-sustainable epoxy materials with tailored mechanical, thermal, and electrical insulation properties suitable for coatings, adhesives, and lightweight insulation applications.
Keywords: biomaterials; biopolymers and renewable polymers; biosynthesis of polymers; thermoplastics; thermosets